Fiscal policy cycles and public expenditure in developing countries - Ludger Schuknecht (World Trade Organization (WTO), 1998)
The paper studies empirically the fiscal policy instruments by which governments try to influence election outcomes in 24 developing countries for the 1973-1992 period. The study finds that the main vehicle for expansionary fiscal policies around elections is increasing public expenditure rather than lowering taxes, and public investment cycles seem particularly prominent. Institutional mechanisms which constrain discretionary expenditure policies and which strengthen fiscal control are therefore worthwhile considering to prevent opportunistic policy making around elections.
Keywords: F4; E62; H62; 330; Elections; political business cycles; fiscal policies; public expenditure; developing countries